2016
DOI: 10.3945/jn.115.220749
|View full text |Cite
|
Sign up to set email alerts
|

Human Milk Oligosaccharides and Synthetic Galactosyloligosaccharides Contain 3′-, 4-, and 6′-Galactosyllactose and Attenuate Inflammation in Human T84, NCM-460, and H4 Cells and Intestinal Tissue Ex Vivo

Abstract: Galactosyllactose attenuated NF-κB inflammatory signaling in human intestinal epithelial cells and in human immature intestine. Thus, galactosyllactoses are strong physiologic anti-inflammatory agents in human colostrum and early milk, contributing to innate immune modulation. The potential clinical utility of galactosyllactose warrants investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
75
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(82 citation statements)
references
References 45 publications
4
75
1
2
Order By: Relevance
“…. In contrast, arabinoxylan and mixed-linked β-glucans did not affect the basal production of IL-8 by Caco-2 and HT-29 cells (Samuelsen et al, 2011), which is in agreement with the unaltered basal expression of proinflammatory mediators in human colonic epithelial cells incubated with pooled HMOs (Newburg, Ko, Leone, & Nanthakumar, 2016).…”
Section: Dietary Fibre Interaction With the Epidermal Growth Factorsupporting
confidence: 82%
“…. In contrast, arabinoxylan and mixed-linked β-glucans did not affect the basal production of IL-8 by Caco-2 and HT-29 cells (Samuelsen et al, 2011), which is in agreement with the unaltered basal expression of proinflammatory mediators in human colonic epithelial cells incubated with pooled HMOs (Newburg, Ko, Leone, & Nanthakumar, 2016).…”
Section: Dietary Fibre Interaction With the Epidermal Growth Factorsupporting
confidence: 82%
“…Previous studies have indicated that specific oligosaccharides can modulate multiple functions of intestinal epithelial cells, in vitro , in vivo and ex vivo (He et al., ; Holscher, Davis, & Tappenden, ; Kuntz et al., ; Kuntz, Kunz, & Rudloff, ; Newburg et al., ; Ortega‐Gonzalez et al., ; Zenhom et al., ). 3’‐sialyllactose and fructooligosaccharides were demonstrated to inhibit baseline chemokine expression and release from the Caco‐2 human intestinal cell line (Zenhom et al., ), while pooled HMOs and synthetic galactosyloligosaccharides were demonstrated to inhibit TNFα and salmonella induced chemokine release from human intestinal cell lines and immature intestinal tissue (Newburg et al., ), but did not appear to alter baseline levels. Similarly, 2’FL was demonstrated to inhibit E.coli induced IL‐8 release through a mechanism involving down‐regulation of the LPS receptor complex component CD14 (He et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Most of these beneficial effects depend on the specific structures of HMOs, with clear distinctions between nonsialylated (neutral) and sialylated (acidic) oligosaccharides (van Hoffen et al., ). Indeed, previous studies have identified that synthetic, plant based and milk derived oligosaccharides can modulate multiple signaling pathways in intestinal epithelial cells, where they have been demonstrated to both inhibit (He et al., ; Newburg, Ko, Leone, & Nanthakumar, ; Zenhom et al., ) and enhance (Ortega‐Gonzalez et al., ) responses to inflammatory signals associated with infection. Such studies suggest the possibility of multiple HMOs having distinct functions, including modulation of various inflammatory signaling pathways.…”
Section: Introductionmentioning
confidence: 99%
“…One approach to prevention is through changing the infant diet, as NEC risk is known to be significantly lower in breastfed infants due to protection provided by various breastmilk components . One such component is human milk oligosaccharides (HMOs), a highly abundant group of indigestible oligosaccharides (5–15 g L –1 ) that: i) stimulate growth of gut commensals, ii) prevent adhesion of enteropathogens, and iii) modulate host immunity . In humans, reduced HMO exposure during the first month of life is linked to the development of NEC .…”
Section: Introductionmentioning
confidence: 99%